Fintech, Female Employment, and Gender Inequality - Loko, Boileau (IMF Working Papers; Working Paper, 2022)
Fintech, which delivers financial services digitally, promises to promote financial inclusion and close the gender gap. Using a novel fintech dataset for 114 economies worldwide, this paper shows that fintech adoption significantly improves female employment and reduces gender inequality, the effect being more pronounced in firms without traditional financial access. Fintech not only increases the number and ratio of female employees in the workforce, but also mitigates financial constraints of female-headed firms. Digital divide and poor institutions weaken such benefits. Endogeneity is accounted for by a fixed effects identification strategy. We conclude by providing policy recommendations and outlining avenues for future research.